Patient and healthcare provider reported barriers and enablers to virtual or remote-only follow-up models for cardiovascular implantable electronic devices: protocol for a qualitative framework synthesis - Shannon E. Kelly; Tammy J. Clifford; Becky Skidmore; David Birnie; Ratika Parkash; George A. Wells (Systematic Reviews, 2020)
Abstract Background Virtual care models are used to follow-up patients with cardiovascular implantable electronic devices (CIED), including pacemakers, implantable cardioverter defibrillators, and cardiac resynchronization therapy. There is increasing interest in the expansion of virtual, or even remote-only, CIED care models to alleviate resource and economic burden to both patients and specialty device clinics and to maintain or improve equity and access to high-quality cardiovascular care. This qualitative framework synthesis aims to identify barriers and enablers to virtual care models from both the perspective of the patient and device clinics. How setting, context, equity factors or other aspects influence these factors, or satisfaction with care, will also be investigated. Methods We will perform a systematic literature search in MEDLINE, Embase, PsycINFO, CINAHL, Proquest Dissertations & Theses, other EBM Reviews, and trial registry databases. Screening will be completed by two independent review authors. Original research articles having a qualitative component (i.e., qualitative, mixed-, or multi-method) are eligible. Study populations of interest are (a) individuals with a CIED or (b) healthcare providers involved in any aspect of virtual or remote follow-up of patients with CIEDs. Eligibility will be restricted to studies published after January 1, 2000 in English or French. Data will be captured using standardized templates based on the domains and constructs of the Theoretical Domains Framework and the Warwick Patient Experiences Framework. The Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research will be applied to all included studies. The GRADE-CERQual approach will be applied to assess and summarize confidence in key findings. Reporting will follow the enhancing transparency in reporting the synthesis of qualitative research (ENTREQ) statement. Detailed descriptive results will be presented, and summary of qualitative findings tables will be produced. Discussion While a number of trials have captured the clinical effectiveness and safety of virtual follow-up for CIEDs, there has been less attention given to factors affecting use and implementation of remote care by patients and healthcare providers or satisfaction with care. Results from this qualitative framework synthesis will provide important lived experience data from both patients and healthcare providers which will be essential to incorporate in clinical guidelines. Systematic review registration PROSPERO CRD42020160533 .